TAFSIR AL-MUKTHASHARAH NAJAMUDDIN AL-THUFI PADA PENYELESAIAN HATESPEECH - Ellys Lestari Pambayun (Institut PTIQ Jakarta, 2019)
Hate speech or known as hatespeech has been known since the time of the Prophet Adam as and occurs in all the lives of all Prophets in the form of zur, slander, namimah, tajasus, ghibah, hasud, and so on. As a result of this form of negative communication the effects on the prophets and their people cannot be imagined. Hatespeech, which was launched by the infidels against Islam and Muslims or which led to the term 'Islamophobia', apparently also has existed since the time of the Prophet. In the early days of the preaching of the Prophet Muhammad, great hostility and attacks against Islam actually appeared in the midst of Arab society which incidentally was a compatriot of the Prophet himself namely in the Makkiyah period (610-622 AD) led by central figures of Quraish like Abu Jahal and Abu Lahab. This paper aims to analyze the case of hatespeech settlement using mau'dhui or thematic methods through the interpretation of Maslahah Najmuddin Al-Thufi as a product of the decline of Islam in particular, as well as Islamic law that demands reform efforts. The results of the study describe that the utterance of hatred in the ahkam at-Thuffi's interpretation method is considered to be devoid of problems, in contrast to mufasadat or harm. Because al-Thufi carries theories and concepts that are very fundamental in the dimension of human activity, in the context of this negative communication behavior namely the benefit of humans as the highest goal of Islamic shari'ah.